Statistics - Spiegel, Murray R. (Schaum's outline series., 2014)
With 508 solved problems, this book includes: information on frequency distribution, elementary probability theory, elementary sampling theory, statistical decision theory, and analysis of variance; and concise explanation of all course concepts.--